Human rights at the crossroads - Goodale, Mark (Oxford University Press, 2013)
Since the end of the Cold War, there has been a dramatic expansion in both the international human rights system and the transnational networks of activists, development organizations, and monitoring agencies that partially reinforce it. Yet despite or perhaps because of this explosive growth, the multiple statuses of human rights remain as unsettled as ever. Human Rights at the Crossroads brings together preeminent and emerging voices within human rights studies to think creatively about problems beyond their own disciplines, and to critically respond to what appear to be intractable problems.